p-regular Cauchy completions - Darrell C. Kent; Jennifer Wig (International Journal of Mathematics and Mathematical Sciences)
This paper gives a further development of p-regular completion theory, including a study of p-regular Reed completions, the role of diagonal axioms, and the relationship between p-regular and p-topological completions.